APC in the regulation of intestinal crypt fission. - Wasan, H; Park, H; Liu, K; Mandir, N; Winnett, A; Sasieni, P; Bodmer, W; Goodlad, R; Wright, N (1998)
The functional effects of APC (adenomatous polyposis coli gene) germ-line mutations on crypt fission and cell proliferation were investigated in the normal intestine of human familial adenomatous polyposis (FAP) and multiple intestinal neoplasia (MIN) mice. Compared with controls, there was a 19-fold increase in the proportion of crypts in fission in FAP colon [95 per cent confidence interval (CI): 11-32, P < 0.0001], and a 75 and 61 per cent increase in MIN colon (95 per cent CI: 1.08-2.82, P < 0.02) and small bowel, respectively (95 per cent CI: 1.31-1.99, P < 0.001). In marked contrast, no significant differences in intra-cryptal epithelial cell proliferation or mitotic distribution were seen. Furthermore, 10.9 per cent of crypts in FAP were in asymmetrical fission as opposed to only 1 per cent in controls (P = 0.001). The largest relative increases in MIN crypt fission were in the colon (proximal and distal colon:190 per cent, P = 0.02 and 83 per cent, P = 0.01), suggesting that Apc mutations exert their maximal influence site-specifically. However, sites with the highest relative increases were also those with the largest eventual tumour sizes, but not the highest polyp counts. Three-dimensional serial section reconstruction analysis corroborated that FAP adenomas enlarge by crypt fission, which was frequently both asymmetrical and atypical. It is proposed that the absence of an increase in intestinal cell division infers that APC regulates intestinal crypt differentiation, specifically through the crypt cycle. This role appears analogous to the control of axis re-duplication in embryonic development, when downstream targets of APC are over-expressed. It is concluded that in vivo, the major defect in pre-neoplastic intestine harbouring APC mutations is elevated rates of crypt fission, and that this is also the mode by which micro-adenomas enlarge.